2003
DOI: 10.1074/jbc.m207800200
|View full text |Cite
|
Sign up to set email alerts
|

17-Epiestriol, an Estrogen Metabolite, Is More Potent Than Estradiol in Inhibiting Vascular Cell Adhesion Molecule 1 (VCAM-1) mRNA Expression

Abstract: 17-␤ estradiol (17-␤ E 2 ) attenuates the expression of vascular cell adhesion molecule 1 (VCAM-1) in vivo at physiological levels (pg/ml), whereas supraphysiological concentrations of 17-␤ E 2 (ng/ml) are required in vitro. We assessed whether a metabolite of estrogen, which could only be generated in vivo, might be a more potent inhibitor of VCAM-1 expression and thereby explain this discrepancy. We report here that 17-epiestriol, an estrogen metabolite and a selective estrogen receptor (ER) ␤ agonist, is ϳ4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 33 publications
4
44
0
Order By: Relevance
“…It has been reported that 17-epiestriol suppresses the expression of tumor necrosis factor a-induced vascular cell adhesion molecule 1 (Mukherjee et al, 2003). In addition, the urinary concentration of 17-epiestriol was found to positively correlate with the risk of breast cancer (Eliassen et al, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…It has been reported that 17-epiestriol suppresses the expression of tumor necrosis factor a-induced vascular cell adhesion molecule 1 (Mukherjee et al, 2003). In addition, the urinary concentration of 17-epiestriol was found to positively correlate with the risk of breast cancer (Eliassen et al, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…In addition, exposure of endothelial cells to estrogens suppresses the NADPH oxidase activity and thereby the intracellular production of reactive oxygen species (ROS), which is instrumental for the expression of adhesion molecules in response to pro-atherogenic factors (Wagner et al 2001). Experiments using ER agonists and antagonists point to both ERa and ERb as mediators of suppressing effects of E 2 on endothelial activation (Mukherjee et al 2003, Mori et al 2004, Geraldes et al 2006, though again these effects could also be observed in the presence of 2-ME (Kurokawa et al 2007, Dubey & Jackson 2009). …”
Section: Mechanisms Underlying Anti-atherogenic Effects Of Estrogens mentioning
confidence: 99%
“…Western blotting was performed as described previously (14). Briefly, 40 g of protein was transferred onto a polyvinylidene difluoride membrane (Bio-Rad) that was blocked overnight with 5% nonfat dry milk.…”
Section: Western Blotting Of Total and Phosphoproteinsmentioning
confidence: 99%